Knockdown and Knockout of Tissue Factor Pathway Inhibitor in Zebrafish - Raman, Revathi; Fallatah, Weam; Qaryoute, Ayah Al; Ryon, Mia; Jagadeeswaran, Pudur (Thrombosis and Haemostasis, 2022)
Tissue factor pathway inhibitor (TFPI) is an anticoagulant that inhibits factor VIIa and Xa in the blood coagulation pathways. TFPI contains three Kunitz domains, K1, K2, and K3. K1 and K2 inhibit factor VIIa and Xa, respectively. However, the regulation of TFPI is poorly studied. Since zebrafish has become an alternate model to discover novel actors in hemostasis, we hypothesized that TFPI regulation could be studied using this model. As a first step, we confirmed the presence of tfpia in zebrafish using reverse transcription polymerase chain reaction. We then performed piggyback knockdowns of tfpia and found increased coagulation activity in tfpia knockdown. We then created a deletion mutation in tfpia locus using the CRISPR/Cas9 method. The tfpia homozygous deletion mutants showed increased coagulation activities similar to that found in tfpia knockdown. Taken together, our data suggest that tfpia is a negative regulator for zebrafish coagulation, and silencing it leads to thrombotic phenotype. Also, the zebrafish tfpia knockout model could be used for reversing this thrombotic phenotype to identify antithrombotic novel factors by the genome-wide piggyback knockdown method.
Keywords: TFPI; coagulation; zebrafish; knockdown; knockout